Konsep Pemikiran Politik Al Mawardi Dalam Pemilihan Kepala Negara di Indonesia - Muhammad Yasir (Ma'had Aly Raudhatul Ma'arif, 2024)
Leadership is an essential element for any country or societal institution. Without a leader, a nation risks chaos and collapse. Al Mawardi, a prominent Islamic thinker known for his political theories, developed several political concepts to address governance issues. This article employs a library research method, involving the reading and analysis of theoretical materials. The study is descriptive-comparative and aims to explain and contextualize Al Mawardi’s thoughts in the framework of leader selection in Indonesia according to the prevailing laws. Primary legal materials used include Law No. 42 of 2008 on the Presidential and Vice-Presidential Election, as well as Al-Ahkam as-Sultaniyah and as-Siyasah as-Syar’iyah. Al Mawardi recommended two methods for selecting the head of state: first, through the institution of ahl al-halli wa al-aqdi (the legislative body), and second, direct appointment by the previous head of state. During the Old and New Order eras in Indonesia, there was a relevance to Al Mawardi’s views, where the head of state was selected either through representation or direct appointment by the previous head of state. This concept aligns with Al Mawardi’s perspective on the selection of the head of state by ahl al-halli wa al-aqdi. However, the application of Al Mawardi’s ideas did not persist into the Reform era in Indonesia.